Halpern's iteration for strongly relatively nonexpansive mappings in Banach spaces - Suantai,S. (Kyungpook National University, 2015)
We investigate strong convergence of Halpern's iteration for a countable family of strongly relatively nonexpansive mappings in the framework of uniformly convex and uniformly smooth Banach spaces. Our results extend those announced by many authors.